On the Possibility of “Confidence-Building Measures” Implementation with Regard to China and Taiwan - L. Hongyi (Международная аналитика)
The article describes the process which took place before establishment of Shanghai Cooperation Оrganization. Under analysis are negotiations between USSR and China on the issue of border delimitation which resulted in strengthening of mutual trust and creation of control mechanism in the sphere of armaments. The said cooperation in the sphere of regional security can be considered as a model for establishment of the similar mechanism of mutual trust between two shores of Taiwan strait. SCO is a proper model because China is a side of bilateral talks and takes real part in working out confidence-building measures as a foundation of security cooperation. The usage of these measures in the relations between Taiwan and China could become a model for development of intraregional cooperation in the East Asia (Asia-Pacific region)